The Effect of Self-Esteem, Self-Efficacy and Family Social Support on Test Anxiety in Elementary Students: A Path Model - Ali Asghar Bayani (Shiraz University of Medical Sciences, 2016)
Background: Test anxiety is one of the most important variables which affect the mental health of students in primary schools. Therefore, it is crucial to identify the factors that influence test anxiety. Objectives: The current study aimed to investigate the mediation effect of self-esteem on the relationship between self- efficacy social support and test anxiety. Patients and Methods: Participants were 374 elementary students (179 boys; 195 girls) who completed the Rosenberg self-esteem scale, the perceived social support from family, the self-efficacy questionnaire and the test anxiety inventory. The relationships between the variables were examined via path analysis. Data analysis was conducted using descriptive and inferential statistics by statistical package for social sciences (SPSS) and analysis of moment structures (AMOS) software. Results: Findings showed that self-efficacy was negatively related with test anxiety (-0.23, P < 0.01), a significant negative association existed between self-esteem and test anxiety (-0.37, P < 0.01) and there was a negative association between social support and test anxiety (-0.18, P < 0.05). The mediation effect of self-esteem on the relationship between self-efficacy, social support and test anxiety were supported in a path model. Conclusions: These findings support the negative correlation of self-efficacy, social support, and self-esteem with test anxiety. The obtained model is appropriate to explain the test anxiety of elementary students.